SEMBUNG–KLADUAN WATERSHED NITRATE WATER QUALITY - Asriningtyas, Visi; Rahayuningsih, Edia (Bumi Lestari; Vol 12 No 1 (2012), 2012)
Nitrate contaminant in Sembung-Kladuan watershed, Sleman, DIY (Yogyakarta Special Regency), Indonesia was being analyzed during 2005-2006. Discharges of the rivers were also being measured. Nitrate concentrations in the rivers were usually high in wet season, while Nitrate concentrations in the wells were high in late dry season. Nitrate loadings were also being examined. A simple filtration device to clean Nitrate from the wells for drinking water was made from a PVC pipe filled with charcoal and sand. The result of this filter was reduction of Nitrate concentration in the drinking water up to 65%.
Keywords: Nitrate concentration, river, well, simple filtration